Sisyawaytii tarawaytii : sifflements serpentins et autres voix d’esprits dans le chamanisme quechua du haut Pastaza (Amazonie péruvienne) - Andréa-Luz Gutierrez-Choquevilca (Journal de la Société des Américanistes)
Sisyawaytii tarawaytii : snake hissing and other spirit voices in Quechua shamanism of the Peruvian Amazon (Pastaza). The article analyzes the sound symbolic and musical means of addressing spirits in Quechua ritual songs, in both therapeutical and cynegetical contexts. Adopting a pragmatic perspective, the author describes the learning context of ritual knowledge and pays close attention to the embedding of spirit voices in ritual discourse. A linguistic analysis, sensitive to the discursive variations, shows that this technique of quotation of a non-human voice, observed during the transmission of ritual songs, has a remarkable echo in its own poetic structure. Through the study of these enunciative devices, the author demonstrates that the indexical use of sound symbolism plays a key role in the performance achieved, allowing the hunter-shaman to lend his voice to the spirits invoked. The emphasis on the strategic use of acoustic masks in ritual interactions could open new perspectives for research on Amerindian ritual discourses.